The Italian Version of the Inventory of Interpersonal Problems (IIP-32): Psychometric Properties and Factor Structure in Clinical and Non-clinical Groups - Lo Coco, Gianluca; Mannino, Giuseppe; Salerno, Laura; Oieni, Veronica; Di Fratello, Carla; Profita, Gabriele; Gullo, Salvatore (Frontiers in Psychology, 2018)
All versions of the Inventory of Interpersonal Problems (IIP) are broadly used to measure people’s interpersonal functioning. The aims of the current study are: a) to examine the psychometric properties and factor structure of the Italian version of the Inventory of Interpersonal Problems – short version (IIP-32); and b) to evaluate its associations with core symptoms of different eating disorders. 1223 participants (n = 623 non-clinical and n = 600 clinical participants with eating disorders and obesity) filled out the Inventory of Interpersonal Problems –short version (IIP-32) along with measures of self-esteem (Rosenberg Self-Esteem Scale, RSES), psychological functioning (Outcome Questionnaire, OQ-45) and eating disorders (Eating Disorder Inventory, EDI-3). The present study examined the eight-factor structure of the IIP-32 with Confirmatory Factor Analysis (CFA) and Exploratory Structural Equation Modeling (ESEM). ESEM was also used to test the measurement invariance of the IIP-32 across clinical and non-clinical groups. It was found that CFA had unsatisfactory model fit, whereas the corresponding ESEM solution provided a better fit to the observed data. However, six target factor loadings tend to be modest, and ten items showed cross-loadings higher than .30. The configural and metric invariance as well as the scalar and partial strict invariance of the IIP-32 were supported across clinical and non-clinical groups. The internal consistency of the IIP-32 was acceptable and the construct validity was confirmed by significant correlations between IIP-32, RSES and OQ-45. Furthermore, global interpersonal difficulties were consistently associated with core eating disorder symptoms, whereas interpersonal styles that reflect the inability to form close relationships, social awkwardness, the inability to be assertive, and a tendency to self-sacrificing were positively associated with general psychological maladjustment. Although further validation of the Italian version of the IIP-32 is needed to support these findings, the results on its cross-cultural validity are promising.